2012
DOI: 10.1002/lary.22148
|View full text |Cite
|
Sign up to set email alerts
|

Tissue remodeling gene expression in a murine model of chronic rhinosinusitis

Abstract: Objective/Hypothesis The Matrix Metalloproteinase (MMP), Fibroblast Growth Factor (FGF) and Bone Morphogenetic Protein (BMP) families regulate tissue remodeling in many normal and pathophysiologic processes. We hypothesize that induction of chronic sinonasal inflammation will be associated with changes in regulation of these tissue remodeling cytokines. Methods Balb/c mice aged 8–12 weeks were sensitized and treated with intranasal Aspergillus fumigatis (AF) three times per week for 1 week, 3 weeks, 2 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(36 reference statements)
2
20
1
Order By: Relevance
“…The above studies, 24,26,27 along with our current investigation, appear to conflict with previous murine studies reported by Sautter et al, in which FGF-2 was down-regulated at one and three weeks in a murine model of CRS [28]. However, there are several limitations to direct comparison of the human and mouse experimental models.…”
Section: Discussioncontrasting
confidence: 84%
“…The above studies, 24,26,27 along with our current investigation, appear to conflict with previous murine studies reported by Sautter et al, in which FGF-2 was down-regulated at one and three weeks in a murine model of CRS [28]. However, there are several limitations to direct comparison of the human and mouse experimental models.…”
Section: Discussioncontrasting
confidence: 84%
“…Its specific role in bone remodeling in CRS patients is not clear, whereas the BMP family was shown to play a role in tissue remodeling. Some members of the BMP family were shown to be reduced or increased in patients with chronic sinusitis in several studies . The consideration of GDF‐5 having a role in bone remodeling was enhanced by one of our study results, which showed that GDF‐5 was released more in osteitic bone tissue when compared to the mucosa in the experimental group (FC = 9.24).…”
Section: Discussionsupporting
confidence: 48%
“…28,29 Briefly, inflammation was assessed by light microscopic examination. The control and OE tissue were examined in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%